2009
DOI: 10.1111/j.1365-294x.2009.04150.x
|View full text |Cite
|
Sign up to set email alerts
|

Polygyny can increase rather than decrease genetic diversity contributed by males relative to females: evidence from red deer

Abstract: Polygyny is expected to erode genetic variability by reducing the diversity of genetic contribution of males to the next generation, although empirical evidence shows that genetic variability in polygynous populations is not lost as rapidly as expected. We used microsatellite markers to study the genetic variability transmitted by mothers and fathers to offspring during a reproductive season in wild populations of a polygynous mammal, the red deer. Contrary to expectations, we found that males contributed more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 69 publications
1
23
0
Order By: Relevance
“…Interestingly, experimental studies of Drosophila harems have produced inbreeding values similar to those we report for Peary caribou [71] and to values observed in Sable Island horses (population subdivision II F IS  = 0.113) [73] and Arctic wolves (F IS  = 0.629) [60]. However, F IS values in most free-living ungulates are low [74][77] and the Peary caribou breeding system is not sufficiently well-studied [33] to draw clear conclusions.…”
Section: Discussionsupporting
confidence: 69%
“…Interestingly, experimental studies of Drosophila harems have produced inbreeding values similar to those we report for Peary caribou [71] and to values observed in Sable Island horses (population subdivision II F IS  = 0.113) [73] and Arctic wolves (F IS  = 0.629) [60]. However, F IS values in most free-living ungulates are low [74][77] and the Peary caribou breeding system is not sufficiently well-studied [33] to draw clear conclusions.…”
Section: Discussionsupporting
confidence: 69%
“…Nonetheless, if there is mate choice and the inbreeding load is high, females may prefer immigrant males, therefore encouraging male dispersal (Lehmann & Perrin 2003). Inbreeding avoidance seems unlikely to explain our results because the critical factors identified by theory (the mating system and the sex disparity in reproductive investment) do not change over the spatial scale of our sampling area It is also difficult to see how female dispersal in one region and male dispersal in an adjacent area would be effective at avoiding inbreeding (but see Perez-Gonzalez et al 2009). Additionally, our genetic analyses provide no evidence of inbreeding (as measured by F IS : Lane 2009) and we found no significant correlations between our measures of sex-specific genetic diversity and sex bias in dispersal.…”
Section: Discussionmentioning
confidence: 86%
“…However, female aggregation could also favor processes that maintain genetic diversity. For red deer in Spain, Pérez-González et al (2009) showed that the level of polygyny was positively associated with a higher transmission of genetic variability by the paternal lineage compared with the maternal lineage, which was likely related to the advantage of heterozygous males in the competition for mates (Meagher et al 2000, Slate et al 2000. Additionally, aggregation of individuals at certain areas may favor female mate choice for dissimilar males, which has been shown to occur in Iberian red deer ).…”
Section: Discussionmentioning
confidence: 92%